1971
DOI: 10.1007/bf02544669
|View full text |Cite
|
Sign up to set email alerts
|

Odor and flavor responses to additives in edible oils

Abstract: The odor threshold was determined for a series of unsaturated ketones, secondary alcohols, hydrocarbons and substituted furans added to bland edible oil. Odor thresholds were taken as the point where 50% of a 15-to 18-member taste panel could detect an odor difference from the control oil. These additives are oxidative products of fats, but the concentrations investigated were far below any level associated with an identifying odor or taste of the additive per se. Odor, rather than flavor, was selected as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…The low flavour threshold vinyl alcohol, l-octen-3-01, has been reported to be responsible for the mushroom note in deteriorated milk fat and dairy products (Downey, 1969). Many workers (Hoffmann, 1962;Badings, 1970;Stark and Forss, 1964;Frankel, 1983) have identified the presence of l-octen-3-01 from oxidised methyllinoleate, Kellard et al (1985); d Badings (1970); < Evans et al (1971) deteriorated butter and soyabean oil. The reaction scheme for the formation of this vinyl alcohol from arachidonate 12-hydroperoxide has already been described in Figure 6.14.…”
Section: Alcoholsmentioning
confidence: 95%
See 1 more Smart Citation
“…The low flavour threshold vinyl alcohol, l-octen-3-01, has been reported to be responsible for the mushroom note in deteriorated milk fat and dairy products (Downey, 1969). Many workers (Hoffmann, 1962;Badings, 1970;Stark and Forss, 1964;Frankel, 1983) have identified the presence of l-octen-3-01 from oxidised methyllinoleate, Kellard et al (1985); d Badings (1970); < Evans et al (1971) deteriorated butter and soyabean oil. The reaction scheme for the formation of this vinyl alcohol from arachidonate 12-hydroperoxide has already been described in Figure 6.14.…”
Section: Alcoholsmentioning
confidence: 95%
“…The reaction scheme for the formation of this vinyl alcohol from arachidonate 12-hydroperoxide has already been described in Figure 6.14. Evans et al (1971) have reported the odour threshold of l-octen-3-ol in cottonseed oil to be 0.9 mglkg, and that of I-hexen-3-01 to be 0.5 mglkg. When present at a concentration of 2 mglkg, l-octen-3-ol produced musty/foreign odour, while the latter gave a rubbery/rancid flavour.…”
Section: Alcoholsmentioning
confidence: 97%
“…Threshold values found for each were very low, with oct-l-en-3-one being detected at approximately 10 ppb (Hammond and Hill, 1964;Hill and Hammond, 1965). Compounds found to contribute to oxidized flavor in soybean oil included 1-decyne and pentyl furan, with threshold values reported at 0.1 ppm and 1 ppm, respectively (Evans et al, 1974). Other hydrocarbons and alcohols were tested for flavor responses and the threshold of oct-l-en-3-ol measured at 0.1 ppm.…”
Section: R-c-r ^ R-c-r R-c-r + R Oh R-c-r + R R« + R-c=0 R-c-r + R IImentioning
confidence: 95%
“…Several classes of compounds have been implicated in off-flavor development of deteriorating oils. Flavor descriptions and thresholds were studied for many of these (Evans et al, 1974;Badings, 1960;Keppler, 1977;Selke et al, 1975). Duin (1960) identified the following classes of carbonyls as contributing to offflavor in butter; saturated aldehydes (C^ -C^g), 2-enals (C^ ~^ll^ ' 2,4-dienals (C^ -C^^^), enals with the double bond not in the 2-position (Cg -C^g), and dienals with a double bond in non-conjugated position to the 2-enal configuration (Cg -C^g).…”
Section: R-c-r ^ R-c-r R-c-r + R Oh R-c-r + R R« + R-c=0 R-c-r + R IImentioning
confidence: 99%
See 1 more Smart Citation